2022
DOI: 10.1007/s00163-022-00402-2
|View full text |Cite
|
Sign up to set email alerts
|

Studying interaction density in co-design sessions involving spatial augmented reality

Abstract: The participation of end-users in co-design sessions has always been challenging. Despite a long history of trials and research, finding the best way to go about this form of collaboration in early innovation phases is still an open question for many companies. At the cutting edge of innovation, design agencies are becoming increasingly involved in co-design today. Direct face-to-face collaboration with end-users is a key factor for the success of codesign, and ICT solutions must therefore allow active involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…-This technology also provides good collaborative tools for evaluation phases between designers and other stakeholders that tend to reduce design iterations and allows the early identification of design errors and defects. (Porter et al, 2010), (Marner et al, 2011), (Irlitti and von Itzstein, 2013), (O'Hare et al, 2018) -Some studies also showed that the technology improves shared understanding and reduces the communication and language barriers (Verlinden, 2012), (Ben Guefrech et al, 2022).…”
Section: Spatial Augmented Reality Technology In Co-designmentioning
confidence: 99%
See 2 more Smart Citations
“…-This technology also provides good collaborative tools for evaluation phases between designers and other stakeholders that tend to reduce design iterations and allows the early identification of design errors and defects. (Porter et al, 2010), (Marner et al, 2011), (Irlitti and von Itzstein, 2013), (O'Hare et al, 2018) -Some studies also showed that the technology improves shared understanding and reduces the communication and language barriers (Verlinden, 2012), (Ben Guefrech et al, 2022).…”
Section: Spatial Augmented Reality Technology In Co-designmentioning
confidence: 99%
“…We are now going to look at this particular aspect. (O'Hare et al, 2018) and (Ben Guefrech et al, 2022) carried out studies highlighting the benefits of SAR systems to support design activities. The first assessed the impact of SAR technology on the novelty and quality of ideas generated compared with traditional design situations.…”
Section: Spatial Augmented Reality Technology In Co-designmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying virtual roaming technology in architectural design, it can present a threedimensional simulation of urban landscapes, residential landscapes, interior design, and historical buildings. (6) Ben Guefrech, for his part, (18) posits that user participation in collaborative design sessions has always been a challenge. Despite research, finding a suitable way to implement co-design in the early stages of innovation remains problematic.…”
Section: Applicationsmentioning
confidence: 99%